Antitumor bioactivity of porphyran extracted from Pyropia yezoensis Chonsoo2 on human cancer cell lines. (31st August 2019) - He, Dan; Wu, Siya; Yan, Liping; Zuo, Jihui; Cheng, Yang; Wang, Hanfei; Liu, Jian; Zhang, Xu; Wu, Mingjiang; Choi, Jong‐il; Tong, Haibin
Abstract: BACKGROUND: Pyropia yezoensis, rich in porphyran, is a medicine‐edible red alga. In the present study, the physicochemical characteristics, conformational states and antitumor activities of a novel porphyran extracted from the high‐yield algal strain Pyropia yezoensis Chonsoo2 and its two degraded derivatives by gamma irradiation were investigated. RESULTS: Pyropia yezoensis porphyran is a water‐soluble, triple‐helical sulfated hetero‐galactopyranose, named PYP. PYP was degraded by gamma irradiation at 20 kGy and 50 kGy, giving two low molecular weight derivatives comprising PYP‐20 and PYP‐50, respectively. PYP with a higher molecular weight has a solution conformation different from PYP‐20 and PYP‐50. Three porphyrans had no toxicity in normal human liver cells (HL‐7702) and showed antitumor effects on Hep3B, HeLa and MDA‐MB‐231. They had better antitumor against HeLa cells, exhibiting a similar inhibition ratio compared to 5‐fluorouracil, with PYP especially exhibiting a higher inhibition ratio than 5‐fluorouracil. With respect to HeLa cells, the different antitumor activities might be related to porphyran molecular weight and solution conformation. Furthermore, the HeLa cell cycle was blocked in the G2/M phase after PYP treatment, leading to cell proliferation inhibition. The induction of cell cycle arrest was related to the changes in the expression of p21, p53, Cyclin B1 and cyclin‐dependent kinase 1. CONCLUSION: Pyropia yezoensis porphyran, as applied to medicine and functional food, could potentially be used as a non‐toxic natural adjuvant in cancer therapy. © 2019 Society of Chemical Industry